(untitled) (New Jersey, 2003)
This volume contains papers describing state-of-the-art technology for advanced multimedia systems. It presents applications in broadcasting, copyright protection of multimedia content, image indexing and retrieval, and other topics related to computer vision.
Keywords: Multimedia systems,Digital media